2017
DOI: 10.2320/matertrans.maw201702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crack Size Distribution and Specimen Length on the Correlation between <i>n</i>-Value and Critical Current in Heterogeneously Cracked Superconducting Tape

Abstract: A Monte Carlo simulation study was carried out to reveal the effects of crack size distribution and specimen length on the correlation between n-value and critical current in heterogeneously cracked superconducting tapes. First, it was shown that, with increasing distribution width of crack size, the distribution widths of critical current and n-values increase, and, the average critical current-value and average n-value of specimens decrease. Also, it was shown that the decrease in average n-value with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We define the current transfer length as s (¹ L 0 ), I c and n-value of the sections in the non-cracked state as I c0 and n 0 , respectively, and the critical electric field for determining the critical current as E c (= 1 µV/cm in this work). We express the VI curve of the cracked section (L 0 = 1.5 cm) as 2,3,8,9,15,16) V…”
Section: Calculating VI Curves Of Sections With the Montementioning
confidence: 99%
See 2 more Smart Citations
“…We define the current transfer length as s (¹ L 0 ), I c and n-value of the sections in the non-cracked state as I c0 and n 0 , respectively, and the critical electric field for determining the critical current as E c (= 1 µV/cm in this work). We express the VI curve of the cracked section (L 0 = 1.5 cm) as 2,3,8,9,15,16) V…”
Section: Calculating VI Curves Of Sections With the Montementioning
confidence: 99%
“…7,11,12) We have studied the I c and n-value of both coated and filamentary tapes 2,3,7,16) experimentally and analytically by applying a current shunting model at cracks. 10) We have been developing a Monte Carlo simulation method 8,9) combined with the current shunting model at cracks to systematically obtain a wide range of data about the effects of crack size distribution and specimen length on I c and n-values. We have shown that this simulation method 8,9) reproduces the experimental observation that the local information about critical current values in a specimen is diluted in longer specimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation of V c to I c , K eq and V RE and the relation of I c to L p,smallest and V RE in the smallest ligamentsection are expressed by eqs. (8) and (9) from eqs. (7) and (2), respectively: Current,…”
Section: Number Of the Sections Equivallent To The Smallest Ligament mentioning
confidence: 99%
“…In the same way, substituting K eq = K eq,ave = N, I c = I c,lower,ave , L p,smallest = L p,smallest,ave and corresponding L-value into eqs. (8) and (9) From eq. (14), the effects of the difference in crack size among the sections on the increase in average REBCOtransported current in the ligament part, ¦I RE,ave , and the increase in average shunting current in the cracked part ¦I s,ave in the largest crack-section were evaluated.…”
Section: Analysis Of the Increment Of Critical Current Inducedmentioning
confidence: 99%